El concepto de justicia y su fundamento. Un análisis de los consensos en J. Rawls desde la perspectiva del nuevo derecho natural en Carlos Massini. (2013)
The reflection on the foundations of the theory of justice in the contemporary debate involves adecision of the principles for defining the material criteria of the just. This definition of the criteria of justice goes hand in hand with the methodological debate ranging from the attempt to replicate the formulation of an empirical science to the identification of some of the elements in the ancient background in the analysis of reason in Hume.One of the representative explanations of the theories of justice is that of John Rawls; who proposes a theory of public justice in a pluralistic society. The realization of this fact; leads the author to postulate the idea that to reach the just requires a formal procedure. This would be the way to meet the claim to ensure the reasonableness of these principles through an overlapping consensus. Another sector of the doctrine called the new natural law ; asks about the relevance of basing the contents of justice. This line of analysis is represented by the legal philosopher Carlos Massini; who argues that the idea of consensus in Rawls incurs in the so-called proceduralist fallacy . Similarly; Massini said that the Rawlsian proposal involves a split in the spheres of life of the person. This division can be seen in the social order resulting from the allocation of the ideas of good to the private sphere and the conceptions of justice to public discussion. This proposal of social structure about the good and the just might call into question the ability of these consensus motivation for citizens to act honestly.